Amaranth BRS Alegria: alternative for diversification of cropping systems - Spehar, Carlos Roberto; Teixeira, Danielly Leite; Cabezas, Waldo Alejandro Rúben Lara; Erasmo, Eduardo Andrea Lemus (Pesquisa Agropecuaria Brasileira, 2003)
Diversification of production systems depends on rapid growth, tolerance to hydric stress, biomass production, nutrient cycling and human and animal utilization. The grain amaranth species Amaranthus caudatus, A. cruentus and A. hypochondriacus, with light seed colour and no dormancy, present these characteristics. They are distinguishable from the weeds A. spinosus, A. hybridus, A. blitum and A. viridis, with dark and dormant seeds. Their grains, with excellent protein quality, can be used in gluten-free special diets and livestock feed. The A. cruentus BRS Alegria, the first recommendation for grain production systems in Brazil, originated from mass selection in the variety AM 5189 of the United States. In double-cropping, after soybeans, it showed average yield of 2,359 kg ha-1 for grain and of 5,650 kg ha-1 for total biomass, in 90 days from emergence to maturity.